2008
DOI: 10.1080/00365520802179933
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ADAMTS13 activity parallels the APACHE II score, reflecting an early prognostic indicator for patients with severe acute pancreatitis

Abstract: Plasma ADAMTS13:AC was closely related to the APACHE II score. This intimate relationship may serve as an early prognostic indicator for SAP patients. The imbalance between decreased ADAMTS13:AC and increased UL-VWFM could contribute to SAP pathogenesis through enhanced thrombogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The other variables used in the study, such as use of mechanical ventilation, length of stay (LOS), vasopressor agents and number of organ failure on admission, also showed correlations with low ADAMTS13 levels but these correlations were not statistically significant. The positive correlation between ADAMTS13 and APACHE II has been shown previously, but this was done in patients with severe acute pancreatitis [25].…”
Section: Discussionmentioning
confidence: 95%
“…The other variables used in the study, such as use of mechanical ventilation, length of stay (LOS), vasopressor agents and number of organ failure on admission, also showed correlations with low ADAMTS13 levels but these correlations were not statistically significant. The positive correlation between ADAMTS13 and APACHE II has been shown previously, but this was done in patients with severe acute pancreatitis [25].…”
Section: Discussionmentioning
confidence: 95%
“…10,11,13,26,27 Elevated VWF levels in plasma in these syndromes may be the result of enhanced release of ULVWF and reduced processing of ULVWF and/or VWF by ADAMTS13. The importance of reduced ADAMTS13 activity in plasma in these diseases or other chronic inflammatory conditions is not known.…”
Section: Discussionmentioning
confidence: 99%
“…7 In distinction, deficiency of ADAMTS13 increases plasma levels of ULVWF and causes thrombotic thrombocytopenic purpura, a disorder of thrombotic microangiopathy. 8 Several epidemiologic studies have demonstrated reduced plasma ADAMTS13 activity in inflammatory conditions, including aging, 9 systemic inflammation, 10 pancreatitis, 11 and sepsis. 12,13 It remains uncertain, however, whether ADAMTS13 contributes to disease pathogenesis or rather simply serves as an inflammation-associated marker.…”
Section: Introductionmentioning
confidence: 99%
“…The elevated plasma VWF level is primarily a consequence of endothelial cell activation, but other mechanisms may be involved. Several recent studies have shown that systemic inflammation is also associated with reduced activity of the VWF-processing enzyme ADAMTS13 activity in syndromes such as acute systemic inflammation caused by endotoxin, 9 acute pancreatitis, 10 severe sepsis and septic shock, 11 sepsis-induced disseminate intravascular coagulation, 12 and sepsis-induced organ dysfunction. [13][14][15] It is therefore likely that in addition to enhanced release of VWF, delayed or reduced VWF processing by ADAMTS13 contributes to the elevated level and adhesiveness of VWF in these inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%